2019
DOI: 10.1002/jcb.28883
|View full text |Cite
|
Sign up to set email alerts
|

A 4‐gene panel predicting the survival of patients with glioblastoma

Abstract: Background To identify independently prognostic gene panel in patients with glioblastoma (GBM). Materials and methods The Cancer Genome Atlas (TCGA)‐GBM was used as a training set and a test set. GSE13041 was used as a validation set. Survival associated differentially expression genes (DEGs), derived between GBM and normal brain tissue, was obtained using univariate Cox proportional hazards regression model and then was included in a least absolute shrinkage and selection operator penalized Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Epithelial membrane protein 3(EMP3) is considered to be a tumor suppressor, but this article found that this gene is a prognostic risk gene for LGG. Similar to our results, Haiwei Wang et al also found that EMP3 was associated with the worse prognosis of LGG patients [23] and Xiao-Xia Guo et al discovered EMP3 was also a risk gene in the process of developing a prognostic 4-gene panel for glioblastoma patients [24]. WEE1 G2 checkpoint kinase(WEE1) is reported to be an oncogenic nuclear kinase and a regulator of the G2 checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Epithelial membrane protein 3(EMP3) is considered to be a tumor suppressor, but this article found that this gene is a prognostic risk gene for LGG. Similar to our results, Haiwei Wang et al also found that EMP3 was associated with the worse prognosis of LGG patients [23] and Xiao-Xia Guo et al discovered EMP3 was also a risk gene in the process of developing a prognostic 4-gene panel for glioblastoma patients [24]. WEE1 G2 checkpoint kinase(WEE1) is reported to be an oncogenic nuclear kinase and a regulator of the G2 checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Ma et al have demonstrated that EMP3 -mediated miR-663a inhibits the gallbladder cancer progression via the MAPK/ERK pathway ( 63 ). Recently, the bioinformatics analysis also found that EMP3 was one of the validated gene panel independently and was correlated with the GBM survival ( 64 , 65 ). Another bioinformatics analysis though significant analysis of microarray (SAM) identified that EMP3 could be used to estimate glioma patient prognosis ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AUC of our model in 3 years was 0.85, the highest was 0.93, the smallest AUC was 0.75 such as Figure 11A, and the highest AUC of 8 immune gene signature (Cheng et al) was 0.64 such as Figure 11B [32]. The highest AUC of 4 gene panel of Guo et al was 0.79 (Figure 11C) [33]. On the other hand, comparing the C-index of the three models, our model has the highest C-index, 0.66, and our model is better than the other two models in all aspects.…”
Section: Resultsmentioning
confidence: 98%